2016
DOI: 10.1146/annurev-immunol-041015-055427
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid and Retinoic Acid Receptors as Pleiotropic Modulators of the Immune System

Abstract: Vitamin A is a multifunctional vitamin implicated in a wide range of biological processes. Its control over the immune system and functions are perhaps the most pleiotropic not only for development but also for the functional fate of almost every cell involved in protective or regulatory adaptive or innate immunity. This is especially key at the intestinal border, where dietary vitamin A is first absorbed. Most effects of vitamin A are exerted by its metabolite, retinoic acid (RA), which through ligation of nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
167
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(177 citation statements)
references
References 154 publications
1
167
0
2
Order By: Relevance
“…Retinoic acid, a metabolite of vitamin A, has a wide range of biological activity including regulating immune responses (15). AM80 is a synthetic retinoic acid that is characterized by higher stability and fewer potential adverse effects compared to all-trans retinoic acid, one of the most active physiological members of the retinoid metabolites (16, 17).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Retinoic acid, a metabolite of vitamin A, has a wide range of biological activity including regulating immune responses (15). AM80 is a synthetic retinoic acid that is characterized by higher stability and fewer potential adverse effects compared to all-trans retinoic acid, one of the most active physiological members of the retinoid metabolites (16, 17).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study discovered that lung DCs could also up-regulate the gut-homing integrin α4β in vitro and in vivo (28). A major part of the retinoic acid anti-inflammatory effects depends on the inhibition of Th17 and promotion of Foxp3 + regulatory T cell (Treg) responses (15, 29). Despite a strong implication of retinoic acid’s involvement in the mucosa, much less is known regarding its role in mucosal Th17 and Treg responses in vivo such as in the lung and small intestine-lamina propria (SI-LP).…”
Section: Introductionmentioning
confidence: 99%
“…The expression of RALDH in the intestine is restricted to epithelial cells, macrophages and DCs, and hence these cells are crucial in controlling the availability of RA. Metabolized RA is sensed by ligation of retinoic acid receptors, nuclear receptors that control downstream transcription of RA target genes . The commensal microbiota acts on intestinal macrophages to produce the cytokine IL‐1 β , which in turn induces intestinal innate lymphoid type 3 cells to produce granulocyte–macrophage colony‐stimulating factor and IL‐4, increasing RALDH expression and RA release by macrophages .…”
Section: Intestinementioning
confidence: 99%
“…74 A major part of retinoic acid's anti-inflammatory effects depends on the inhibition of T H 17 and promotion of FOXP3 + Treg responses. 74,75 AM80 is a synthetic retinoic acid that is characterized by higher stability and fewer potential adverse effects compared with all- trans -retinoic acid, one of the most active physiological retinoid metabolites. 76, 77 It has been reported that retinoic acid and AM80 ameliorate many autoimmune responses, including experimental autoimmune myositis, experimental autoimmune encephalitis, and collagen-induced arthritis.…”
Section: Mechanisms By Which Commensals Promote Autoimmunitymentioning
confidence: 99%